2019
DOI: 10.1029/2019jg005226
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Hyporheic Flow, Pore Water Chemistry, and Microbial Community Composition in an Alpine Streambed

Abstract: The hyporheic zone, where surface water and groundwater mix, is an important microbial habitat where biogeochemical reactions influence water quality. We show that spatial variability in hyporheic flow in the East River near Crested Butte, CO, drives heterogeneity in streambed geochemical conditions and microbial community assemblages, but the diversity of microbial assemblages remains nearly constant throughout the reach. In July 2018, we collected approximately 100 pore water samples at 20-cm depth and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 58 publications
9
33
0
Order By: Relevance
“…Sediment Collection. Forty-three sediment samples were collected during August 1 -August 13, 2018 at locations corresponding to pore water sampling locations described in Nelson et al (2019) (Figure 2). The sediment grab samples were collected using a standard shovel, retrieving the top 5-8 cm of sediment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sediment Collection. Forty-three sediment samples were collected during August 1 -August 13, 2018 at locations corresponding to pore water sampling locations described in Nelson et al (2019) (Figure 2). The sediment grab samples were collected using a standard shovel, retrieving the top 5-8 cm of sediment.…”
Section: Methodsmentioning
confidence: 99%
“…The meander has an average channel gradient of 0.01 m/m, an average channel width of 8 m, and flow depths ranging from 3 cm in the riffles to greater than 1 m in pools at baseflow. The reach is underlain by Cretaceous Mancos shale (Nelson et al, 2019).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in floodplain soils that host TRZs and other organic-rich layers, microorganisms have been shown to produce compounds that control redox states, and determine solubility and mobility of contaminants, including metals such as Fe and U (Davis et al, 2006;Mouser et al, 2015). Previous work has indicated that these microorganisms may be distributed based on the geochemical environment in which they reside and its respective seasonal changes (Hug et al, 2015;Danczak et al, 2016a;Nelson et al, 2019), and also that microbial metabolisms in groundwater-influenced soils are interconnected and interdependent (Wrighton et al, 2014;Anantharaman et al, 2016).…”
Section: Key Microbial Taxa Linked To Geochemical Changesmentioning
confidence: 99%
“…Even in water-saturated conditions, the tortuosity and size variability of pores lead to uneven oxygen diffusion rates and, hence, variable oxygenation of pores within the same soil horizon (Fan et al, 2014;Neira et al, 2015;Hu et al, 2018). Finally, differences in seasonal dynamics and stability between microorganisms sampled from soil versus groundwater (Hug et al, 2015;Danczak et al, 2016b;Nelson et al, 2019) imply that a complete view of microbial controls on geochemistry may require both types of samples to be analyzed in floodplain soils, or further work is needed to determine which is more important.…”
Section: Microbial and Geochemical Couplingsmentioning
confidence: 99%